30 pī phatthanākān nayōbāi hǣng chāt dān yā khō̜ng Thai (2524-2554) (Phǣnngān Sāng Konkai Faorawang læ Phatthanā Rabop Yā (Kō̜phō̜yō̜.), Khana Phēsatchasāt, Čhulālongkō̜nmahāwitthayālai, 2011)
Pharmaceutical policy of Thailand, 1981-2011.